Permainan Ular Tangga: Pengembangan Media dalam Pembelajaran Tematik Siswa Kelas V SD/MI - Wulansari, Ririn; Jaya, Wayan Satria; Harjanto, Ambyah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
This study aims to develop the game of snakes and ladders as a medium for thematic learning, as well as to find out its feasibility and the responses of teachers and students at SD Negeri 1 Campang Raya. Researchers use the type of research that is included in the type of research and development or also called Research and Development (R&D). This research leads to the ADDIE development model, which uses 5 steps in research, namely 1) Analysis or analysis 2) Design or design 3) Development or development 4) Implementation or implementation 5) Evaluation or evaluation. The data collection technique is using questionnaires, interviews, observations, and documentation to determine the feasibility of the snake and ladder game, and the responses of students and educators. In this study, the subjects were students of class VB at SDN 1 Campang Raya Bandar Lampung, totaling 22 students. The results of the research developed in the form of a snake and ladder game in thematic learning obtained a percentage level of material expert eligibility 86% and a media expert eligibility percentage rate of 88%, thus meeting the "very feasible" criteria. Then the percentage level of student responses to the media in small-scale trials obtained a percentage rate of 94% and in large-scale trials obtained a percentage rate of 95% thus fulfilling the "very interesting" criteria. And the teacher's response obtained a percentage level of 97% with the criteria of "very interesting". The author can conclude that the game of snakes and ladders is a suitable learning medium to be used as a learning medium, which is especially used in thematic learning for class V, theme 8, sub-theme 3.